The effect of physical activity on health outcomes in people with moderate-to-severe traumatic brain injury: a rapid systematic review with meta-analysis - Liam Johnson; Gavin Williams; Catherine Sherrington; Kavya Pilli; Sakina Chagpar; Aylish Auchettl; Jack Beard; Renee Gill; Gabrielle Vassallo; Nick Rushworth; Sean Tweedy; Grahame Simpson; et al. (BMC, 2023)
Abstract Background In 2020, the World Health Organization (WHO) released the first global physical activity and sedentary behaviour guidelines for children and adults living with disability. The evidence informing the guidelines though is not specific to people living with traumatic brain injury (TBI), but rather comes from other disabling conditions such as Parkinson's disease, and stroke. There remains a clear lack of direct evidence of the effects of physical activity for people living with TBI. The objective of this rapid review was to identify direct evidence of the effect of physical activity on health outcomes in people with moderate-to-severe TBI to inform adaptation of the WHO physical activity guidelines into clinical practice guidelines. Methods We conducted a rapid systematic review with meta-analysis of randomised controlled trials, including people of any age with moderate-to-severe TBI, investigating physical activity interventions compared to either usual care, a physical activity intervention with different parameters, or a non-physical activity intervention. Four databases (CENTRAL, SPORTDiscus, PEDro, Ovid MEDLINE) were searched from inception to October 8, 2021. The primary outcomes were physical function, cognition, and quality of life. Results Twenty-three studies were included incorporating 812 participants (36% females, majority working-age adults, time post-TBI in studies ranged from 56 days (median) to 16.6 years (mean)). A range of physical activity interventions were evaluated in rehabilitation (n = 12 studies), community (n = 8) and home (n = 3) settings. We pooled data from the end of the intervention for eight outcomes. Participation in a virtual reality physical activity intervention improved mobility, assessed by the Community Balance and Mobility Scale (range 0 to 96; higher score indicates better mobility) more than standard balance training (two studies, 80 participants, Mean Difference = 2.78, 95% CI 1.40 to 4.16; low certainty evidence). There was uncertainty of effect for the remaining outcomes, limited by small sample sizes, diverse comparators and a wide range of outcome measures. Conclusion This review consolidates the current evidence base for the prescription of physical activity for people with moderate-to-severe TBI. There remains a pressing need for further rigorous research in order to develop practice guidelines to support clinical decision-making when prescribing physical activity in this population.